Antitumor Agents. 3. Design, Synthesis, and Biological Evaluation of New Pyridoisoquinolindione and Dihydrothienoquinolindione Derivatives with Potent Cytotoxic Activity - Bolognese, Adele; Correale, Gaetano; Manfra, Michele; Lavecchia, Antonio; Mazzoni, Orazio; Novellino, Ettore; La Colla, Paolo; Sanna, Giuseppina; Loddo, Roberta (Journal of medicinal chemistry, 2004)
New antiproliferative compounds, the 1-aryl-3-ethoxycarbonyl-pyrido[2,3-g]isoquinolin-5,10-diones (PIQDs, 1−7), were designed on the basis of a molecular model obtained by aligning the common quinolinquinone substructure of 5H-pyrido[3,2-a]phenoxazin-5-one (PPH) and some known anticancer agents. A Diels−Alder reaction between quinolin-5,8-dione (QD) and a 2-azadiene, formed by demolition of 2-aryl-1,3-thiazolidine ethyl esters (T compounds), was used to produce 1−7 and the isomeric 1-aryl-3-ethoxycarbonylpyrido[3,2-g]isoquinolin-5,10-diones (8−14). Two other compounds, the 3-amino-3-ethoxycarbonyldihydrothieno[2,3-g]quinolin-4,9-dione (15) and the 3-amino-3-ethoxycarbonyldihydrothieno[3,2-g]quinolin-4,9-dione (16), arising from a 1,4 Michael reaction of QD with a thiolate species formed by opening of T compounds, were recovered from the reaction mixture. The antiproliferative activity of 1−16 was evaluated against representative human liquid and solid neoplastic cell lines. The IC50 of these compounds had median values in the range 2.00−0.01 μM, with 2−4 and 15 exhibiting significantly higher in vitro cytotoxic activity. Compound 2, also evaluated against KB subclones (KBMDR, KB7D, and KBV20C), was shown to be scarcely subject to the MDR1/P-glycoprotein drug efflux pump responsible for drug resistance. The noncovalent DNA-binding properties of PIQDs were examined using UV−vis and 1H NMR spectroscopy experiments. Accordingly, these compounds were confirmed to have an ability to intercalate into double-stranded DNA by topoisomerase I superhelix unwinding assay. Interesting structure−activity relationships were found. Three important features seem to contribute to the cytotoxic activity of these anticancer ligands:  (i) the DNA intercalating capability of the three-cyclic quinonic system, typical of this class of compounds, (ii) the position of the pendant phenyl ring that, according to the superimposition model, must occupy the same area of the corresponding benzo-fused ring A of PPH, and (iii) the effect of electron-withdrawing substituents on the phenyl ring, which can contribute improving the π−π stacking interactions between ligand and DNA base pairs. Besides, a mechanism of action suspected to involve topoisomerases could be hypothesized to interpret the antiproliferative activity of the thienoquinolindione 15, which can be regarded as a cyclic cysteine derivative.